Is cancer a metabolic rebellion against host aging?: In the quest for immortality, tumor cells try to save themselves by boosting mitochondrial metabolism - Ertel, Adam (Landes Bioscience, 2012)
Aging drives large systemic reductions in oxidative mitochondrial function, shifting the entire body metabolically toward aerobic glycolysis, a.k.a, the Warburg effect. Aging is also one of the most significant risk factors for the development of human cancers, including breast tumors. How are these two findings connected? One simplistic idea is that cancer cells rebel against the aging process by increasing their capacity for oxidative mitochondrial metabolism (OXPHOS). Then, local and systemic aerobic glycolysis in the aging host would provide energy-rich mitochondrial fuels (such as L-lactate and ketones) to directly “fuel” tumor cell growth and metastasis. This would establish a type of parasite-host relationship or “two-compartment tumor metabolism,” with glycolytic/oxidative metabolic coupling. The cancer cells (“the seeds”) would flourish in this nutrient-rich microenvironment (“the soil”), which has been fertilized by host aging. In this scenario, cancer cells are only trying to save themselves from the consequences of aging by engineering a metabolic mutiny, through the amplification of mitochondrial metabolism. We discuss the recent findings of Drs. Ron DePinho (MD Anderson) and Craig Thomspson (Sloan-Kettering) that are also consistent with this new hypothesis, linking cancer progression with metabolic aging. Using data mining and bioinformatics approaches, we also provide key evidence of a role for PGC1a/NRF1 signaling in the pathogenesis of (1) two-compartment tumor metabolism and (2) mitochondrial biogenesis in human breast cancer cells.